MAINSTREAM TEACHERSâ ATTITUDE AND APPROACHES TO SUPPORT CHILDRENâS BILITERACY DEVELOPMENT IN AUSTRALIAN CLASSROOM CONTEXT - Muhammad Basri Jafar (TEFLIN, 2010)
Abstract: This article examines the role of mainstream teachers in supporting childrenâs biliteracy development and bilingualism in a public primary school where English is the medium of instruction. It reports a research conducted in a public primary school in Australia. The research employs a longitudinal ethnographic approach to collect data on how the teachers perceive biliteracy and the extent to which the approaches they adopt impact on their biliteracy and bilingualism development. The research result demonstrates that the more supportive the teachers for biliteracy development and bilingualism are, the more constructivist their teaching approach is and the more varied the activities they encouraged in their classrooms to create opportunities for biliteracy and bilingualism engagement and learning are.